Low anterior resection syndrome following different surgical approaches for low rectal endometriosis: A retrospective multicenter study. (19th December 2020) - Bokor, Attila; Hudelist, Gernot; Dobó, Noémi; Dauser, Bernhard; Farella, Marilena; Brubel, Réka; Tuech, Jean‐Jacques; Roman, Horace
Abstract: Introduction: There is increasing evidence that intermediate and long‐term bowel dysfunction may occur as a consequence of radical surgery for rectal deep endometriosis (DE). Typical symptoms include constipation, feeling of incomplete evacuation, clustering of stools, and urgency. This is described in the colorectal surgical literature as low anterior resection syndrome (LARS). Within this, several studies suggested that differences regarding functional outcomes could be favorable to more conservative surgical approaches, that is, excision of endometriotic tissue with preservation of the luminal structure of the rectal wall when compared with classical segmental resection techniques for DE, especially when performed for low DE. Material and methods: A total of 211 patients undergoing rectal surgery for low DE (≤7 cm from the anal verge) in three different tertiary referral centers between October 2009 and December 2018 were retrospectively reviewed regarding major complications and LARS. From the 211 eligible patients, six women were excluded because of loss to follow‐up. Finally, a total number of 205 patients were enrolled for the statistical analysis; 139 with nerve‐ and vessel‐sparing segmental resection (NVSSR) and 66 operated for laparoscopic‐transanal disk excision (LTADE) were included. Gastrointestinal functional outcomes of the two procedures were compared using the validated LARS questionnaire. The median follow‐up time was 46 ± 11 months. As a secondary outcome, the surgical sequelae were examined. Results: We found no statistically significant difference between the incidence of LARS (31.7% and 37.9%, respectively) among patients operated by LTADE when compared with NVSSR ( P = .4). The occurrence of LARS was positively associated with the use of protective ileostomy or colostomy ( P = .02). A higher rate of severe complications was observed in women undergoing LTADE (19.7%) when compared with patients with NVSSR (9.0%, P = .029). Conclusions: LARS is not more frequent after NVSSR when compared with a more conservative approach such as LTADE in patients undergoing rectal surgery for low DE. To confirm our findings prospective studies are required.